KONFLIK INTRAPSIKIS TOKOH UTAMA DALAM NOVEL SEBELAS KARYA TERE LIYE: KAJIAN PSIKOLOGI SASTRA - Maqnuah, Maidatul; Hasbullah Ridwan, Muhammad (Universitas Muhammadiyah Makassar, 2026)
This study examines the intrapsychic conflict of the main character in Tere Liye's novel Sebelas through a literary psychology approach with Sigmund Freud's psychoanalytic theory. The background of the study departs from the phenomenon of human inner struggle reflected in literary works as a reflection of the complexity of personality. The purpose of this study is to uncover the forms and causes of intrapsychic conflict experienced by the character Paul, as well as to explain the self-defense mechanisms in dealing with inner stress and the healing process. This study uses a qualitative descriptive method with primary data sources in the form of the novel text and secondary sources from psychoanalytic theory literature and relevant research. The results show that Paul's inner conflict is triggered by past trauma, guilt, and conflicting moral values between instinctive urges (id) and moral demands (superego), which cause psychological tension. The self-defense mechanisms that emerge include repression, rationalization, projection, aggression, and sublimation, which play a role in the character's emotional healing process. The findings of this study confirm that intrapsychic conflict not only describes psychological suffering but also a therapeutic process towards self-acceptance and emotional maturity, thus enriching the study of modern literary psychology in Indonesia.